Students welcome UMP Menu Kasih set - Siti Nur Azwin, Zulkapri (2022)
PAYA BESAR, 8 July 2022 - Universiti Malaysia Pahang (UMP) introduced UMP Menu Kasih dish set for students on campus in line with the desire of the Ministry of Higher Education (MOHE) so that Higher Education Institutions (IPT) provide food sales on campus with a ceiling price of RM3.50 for each meal through the initiative of Siswa Keluarga Malaysia Food Basket.